2001
DOI: 10.1002/asi.10018
|View full text |Cite
|
Sign up to set email alerts
|

Web page change and persistence—A four‐year longitudinal study

Abstract: Changes in the topography of the Web can be expressed in at least four ways: (1) more sites on more servers in more places, (2) more pages and objects added to existing sites and pages, (3) changes in traffic, and (4) modifications to existing text, graphic, and other Web objects. This article does not address the first three factors (more sites, more pages, more traffic) in the growth of the Web. It focuses instead on changes to an existing set of Web documents. The article documents changes to an aging set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(132 citation statements)
references
References 19 publications
7
119
0
6
Order By: Relevance
“…Subsequent studies by Koehler (2002) However, the authors noted that many Web references were invalid which was an impediment to allowing them to investigate and verify the content of these sources.…”
mentioning
confidence: 99%
“…Subsequent studies by Koehler (2002) However, the authors noted that many Web references were invalid which was an impediment to allowing them to investigate and verify the content of these sources.…”
mentioning
confidence: 99%
“…The study furthermore found that past change was a good judge of future change, this page length was correlated with change, and that the top level domain of a page was correlated with change. Describing the amount of change on the Web has been of significant interest to researchers [44], [46], [47], [48], [49], [50], [52]. Cho and Garcia-Molina [44] crawled around 720,000 pages once a day for a period of four months and seemed at how the pages changed.…”
Section: Literature Surveymentioning
confidence: 99%
“…Estima-se que esse erro ocorre em cerca de 7% dos links (Bigwood, 1999). Numa medida ao longo do tempo, tendo como objeto de estudo uma amostra aleatoriamente selecionada de URL´s, foi demonstrado que somente cerca de 34% dos URL´s permaneciam ativos depois de um período de quatro anos (Koehler, 2002 …”
Section: O Problema De Identificação De Recursos Na Internet -Nome Veunclassified